Geographical distribution and conservation of Cucurbita in Brazil - Fonseca, Maria Aldete; Queiroz, Manoel Abílio de; Lopes, José Flávio; Assis, José Geraldo de Aquino; Romão, Roberto Lisboa; Ramos, et al., Semiramis Rabelo Ramalho (MAGISTRA, 2017)
Abstract: The collection and conservation of the Cucurbita genus in Brazil happened in so dispersed institutions, an assessment of the storage conditions and the genetic diversity is needed, making it possible to identify new priorities for the genus. This work constitutes diagnosis of geographical distribution, storage conditions in situ and ex situ and on genetic diversity of the Cucurbita genus in Brazil. Research was done in herbariums, databases, literature and in situ (expeditions to rural areas and markets) to map the areas of occurrence of the species. During these expeditions, questionnaires were applied to obtain information about the property and genus Cucurbita. Questionnaires were sent to 173 Brazilian institutions regarding the preservation conditions ex situ. A genetic variability of the Cucurbita genus was found in traditional Brazilian agriculture. Collections must be prioritized in the northern and southern regions (all states); the southeastern region, all states, except Minas Gerais; central-west, in Mato Grosso do Sul and Mato Grosso; the northeastern region, the states of Alagoas, Maranhão, Paraíba, Pernambuco, Piauí and Sergipe. Currently 5.545 entries are being conserved in the Germplasm banks, however, C. pepo, C. ficifolia, C. argyrosperma and wild species are poorly represented. The characterization level of conserved entries is low in the ex situ collections. Participative research projects must be financed as a way to stimulate the farmers to continue planting their local varieties. Key words: Pumpkin, Genetic resources, Preservation